Formation of silicate nanoscrolls through solvothermal treatment of layered octosilicate intercalated with organoammonium ions. Issue 27 (28th June 2019) - Asakura, Yusuke; Sugihara, Megumi; Hirohashi, Takeru; Torimoto, Aya; Matsumoto, Takuya; Koike, Masakazu; Kuroda, Yoshiyuki; Wada, Hiroaki; Shimojima, Atsushi; Kuroda, Kazuyuki
Abstract : Silicate nanoscrolls with crystalline walls were prepared by intercalation of layered octosilicate with organoammonium ions and the subsequent solvothermal treatment. Abstract : We report silicate nanoscrolls composed of only SiO4 tetrahedra with crystalline walls for the first time in this study. The procedure consists of the intercalation of layered octosilicate with dioctadecyldimethylammonium bromide ((C18 )2 DMABr) and the subsequent solvothermal treatment of the intercalated material in heptane. The walls of the obtained nanoscrolls are crystalline, which originates from layer crystallinity in the pristine silicate. The direction of rolling up is fixed at the a - or b -axis of the silicate based on the electron diffraction patterns of the nanoscrolls. Desorption of (C18 )2 DMABr, which is present in addition to (C18 )2 DMA cations, from the interlayer during solvothermal treatment is likely related to the nanoscrolling process. Although the yield of nanoscrolls is low, these findings will lead to the re-estimation of many layered silicates intercalated with long-chain alkylammonium compounds as precursors for silicate nanoscrolls with crystalline walls.